Evolution of defects in nanoporous gold with annealing temperature using low-energy positron beam experiments. (20th April 2017) - Lakshmanan, C.; Viswanath, R. N.; Rajaraman, R.; Dash, S.; Amarendra, G.; Sundar, C. S.
Abstract: Defects in nanoporous gold (np-Au) samples, prepared by selective dissolution of silver from a binary Ag75 Au25 alloy, with annealing temperature have been investigated using the positron beam Doppler line shape S -parameter. It is shown that there is an initial formation of vacancy clusters arising due to the aggregation of thermally migrating vacancies up to 473 K, followed by the breakup of these clusters at higher temperatures, coincident with the rapid growth of ligaments. In addition to the defect-specific S -parameter, the low-energy positron beam experiments have also been used to evaluate the variation of the effective positron diffusion length in np-Au with annealing temperature. The variation of effective positron diffusion length with the ligament diameter, d, scales as which points to the diffusion of positrons along the ligament length, that is also substantiated through measurement of the positronium fraction.